1985
DOI: 10.1111/j.1432-1033.1985.tb08867.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the MgATP and MgADP binding sites on the Fe protein of nitrogenase from Azotobacter vinelandii

Abstract: Flow dialysis was used to study the binding of MgATP and MgADP to the nitrogenase proteins of Azotobucter vinelundii. Both reduced and oxidized Av, bind two molecules of MgADP, with the following dissociation constants: reduced Av,, K1 = 0.091 k 0.021 mM and K2 = 0.044 * 0.009 mM; oxidized Av,, K1 = 0.024 k 0.015 mM and K 2 = 0.039 * 0.022 mM. Binding of MgADP to reduced Av, shows positive co-operativity.Oxidized Av, binds two molecules of MgATP with dissociation constants K1 = 0.049 k 0.016 mM and K 2 = 0.18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…From a biochemical standpoint, the low cytosolic [ADP] may favor some aspects of cell metabolism, because it promotes the function of MgATP-using enzymes that are competitively inhibited by MgADP, such as nitrogenase (36) and various kinases (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…From a biochemical standpoint, the low cytosolic [ADP] may favor some aspects of cell metabolism, because it promotes the function of MgATP-using enzymes that are competitively inhibited by MgADP, such as nitrogenase (36) and various kinases (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…rnol Av;' at 22°C (J. Cordewener, unpublished results [13]. Under all conditions gel centrifugation experiments showed that approximately 1 mol MgADP or MgATP was bound/mol Av, (see Table 2).…”
Section: Muter Ialsmentioning
confidence: 99%
“…The higher values were observed with Fe protein with higher activity. Since Fe protein has two MgATP biMing sites [13], it means that when each binding site is converted into a catalytic site in the complex, each site has two turnovers in the burst reaction. Since one of the two adenine-nucleotide-binding sites has a low rate of dissociation of MgADP, it might be possible that this site will be constantly occupied by MgADP after the first molecule of MgATP is hydrolyzed in the pre-steady-state burst reaction.…”
Section: Muter Ialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated dissociation constants reported vary considerably. For the oxidized Fe protein from Azotobacter vinelandii, the K m values (ATP) are between 49 and 290 M; the corresponding values determined for the reduced protein vary between 220 and 1,710 M. Saturation of binding sites is achieved between 0.5 and 1 mM (6). Considering the effective nucleotide concentration range shown in Fig.…”
Section: Discussionmentioning
confidence: 99%